Dampak Pengetahuan Lingkungan pada Generasi Z terhadap Perilaku Pembelian Ramah Lingkungan Studi pada Industri Fashion: Konsep Identitas Pribadi dan Sosial - Muhammad Dikhya Rahman; Dorothy Rouly Haratua Pandjaitan; Angga Febrian (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
Sustainable consumption practices, notably in the fashion sector, are being encouraged by growing environmental consciousness. However, there is still a disconnect between consumers' intentions to purchase environmentally friendly goods and their actual purchasing habits, particularly among Gen Z. This study investigates the relationship between Personal Identity and Social Identity and the intention to purchase eco-friendly products. It also investigates the role of Specific Environmental Knowledge as a moderator and the role of that desire as a mediator for green purchasing behavior. 260 Gen Z respondents who are concerned about the environment were surveyed as part of the study's quantitative methodology. Purposive sampling was used to choose the sample, and PLS-SEM with SmartPLS 4 was used to analyze the data. The study's findings demonstrate that social and personal identities significantly and favorably influence consumers' intentions to make green purchases. However, neither the association between personal identity nor social identity and green buy behavior is mediated by green purchase intention, nor does it significantly impact green purchase behavior. Furthermore, it has not been demonstrated that specific environmental knowledge moderates this link. These results point to an intention-behavior gap, where actual purchasing behavior has not yet been influenced by the intention to purchase eco-friendly products. This study contributes to the body of knowledge regarding Generation Z's green consumer behavior in the fashion sector.